Singlet Oxygen-Induced Mitochondrial Reset in Cancer: A Novel Approach for Ovarian Cancer Therapy - Jorgelindo da Veiga Moreira; Laurent Schwartz; Mario Jolicoeur (Metabolites)
Background/Objectives: This study explores the generation of singlet oxygen (SO) through methylene blue (MB) activation as a metabolic intervention for ovarian cancer. We aimed to examine the role of SO in modulating mitochondrial function, cellular metabolism, and proliferation in ovarian cancer cell lines compared to control cells. Methods: The study utilized two ovarian cancer cell lines, OV1369-R2 and TOV1369, along with ARPE-19 control cells. Following MB treatment and light activation, mitochondrial function and ATP synthesis were assessed. Metabolomic analyses were performed to evaluate changes in central carbon metabolism, particularly focusing on markers of the Warburg effect. Results: TOV1369 cells exhibited a pronounced sensitivity to MB treatment, resulting in significant inhibition of ATP synthesis and reduced proliferation. Metabolomic analysis indicated that MB-induced SO production partially reversed the Warburg effect, suggesting a shift from glycolysis to oxidative phosphorylation. These effects were less pronounced in OV1369-R2 and ARPE-19 cells, correlating with their lower MB sensitivity. Conclusions: MB-generated SO selectively modulates mitochondrial energetics in ovarian cancer cells, driving a metabolic reorganization that curtails their proliferative capacity. This approach, leveraging the bacterial-like features of cancer metabolism, offers a promising therapeutic avenue to induce apoptosis and enhance treatment outcomes in ovarian cancer.